Battery cell, battery device, power consuming device, and energy storage device

CN122930834APending Publication Date: 2026-10-16CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510404831.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是现有技术中难以实现上述性能的同时改善,这成为本领域亟需解决的技术问题

Benefits of technology

[0067]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930834A_ABST
    Figure CN122930834A_ABST
Patent Text Reader

Abstract

The application provides a battery monomer, a battery device, a power utilization device and an energy storage device. The battery monomer comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector, the negative electrode film layer comprises a negative electrode active material, the negative electrode active material comprises a core part and a coating layer at least partially coated on the surface of the core part, the core part comprises microcrystalline graphite, the coating layer comprises amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95. The battery monomer provided by the application has good fast charging performance and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery cell technology, and in particular to a battery cell, battery device, power consumption device and energy storage device. Background Technology

[0002] In recent years, battery cells have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.

[0003] As the market demands for longer driving range and faster charging performance of electrical devices, higher requirements are being placed on the energy density and dynamic performance of individual battery cells. However, existing technologies struggle to simultaneously improve these performance characteristics, making this a pressing technical problem that needs to be solved in this field. Summary of the Invention

[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell that combines high energy density and good fast charging performance.

[0005] The first aspect of this application provides a battery cell, including a positive electrode, a negative electrode, and an electrolyte; the negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the negative electrode film layer includes a negative electrode active material, the negative electrode active material includes a core and a coating layer at least partially covering the surface of the core, the core includes microcrystalline graphite, the coating layer includes amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95.

[0006] The negative electrode active material includes microcrystalline graphite with an amorphous carbon coating. Microcrystalline graphite is isotropic and has fine grains, which helps to increase the number of end faces where active ions can be embedded in the negative electrode active material, thereby enhancing the fast-charging performance of the battery cell. At the same time, controlling the roundness of the negative electrode active material within the range of 0.65-0.95 makes the particle morphology of the negative electrode active material more rounded, reduces bridging between particles, and enhances the slippage between particles under external force, thereby increasing the compaction density of the negative electrode active material. It also reduces the sharp edges of the negative electrode active material, reducing the capacity loss caused by particle breakage, thus jointly achieving an increase in battery energy density.

[0007] In any embodiment, the roundness of the negative electrode active material is 0.75-0.9.

[0008] Controlling the roundness of the negative electrode active material within the range of 0.75-0.9 helps to further reduce capacity loss caused by particle breakage while maintaining the high compaction density of the negative electrode active material, thereby increasing the compaction density and specific capacity of the negative electrode active material and thus improving the energy density of the battery. On the other hand, it helps to improve the tortuosity of the negative electrode film and improve the dynamic performance of the electrode, thereby further improving the fast charging performance of the battery.

[0009] In any embodiment, the R value of the negative electrode active material is 88%-96%, where R = 1. G / (I G +I D ), I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.

[0010] In any embodiment, the R value of the negative electrode active material is 88%-92%, where R = 1. G / (I G +I D ), I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.

[0011] The R-value characterizes the degree of defect and disorder in the negative electrode active material. The smaller the value, the greater the degree of surface defect and the higher the surface disorder of the negative electrode active material. When the R-value of the negative electrode active material is within the above range, the amorphous carbon in the coating layer has a high degree of disorder, which is beneficial to increasing the transport path of active ions and improving the insertion and extraction rate of active ions in the negative electrode active material, thereby improving the fast charging performance of the battery.

[0012] In any embodiment, the orientation degree (OI) of the negative electrode active material is 0.5-4.

[0013] In any embodiment, the orientation degree (OI) of the negative electrode active material is 1.5-3.

[0014] The OI value reflects the disorder of the material. The OI value of the negative electrode active material within the above range shows a strong degree of disorder, that is, the negative electrode active material is isotropic, the fine crystals inside the material are randomly packed, the number of end faces where active ions can be inserted is large, and the insertion speed is improved, which helps to improve the fast charging performance of the battery cell.

[0015] In any embodiment, the thickness of the coating layer is 1-300 nm, and can be selected as 5-200 nm.

[0016] Within the aforementioned range, the thickness of the coating layer is beneficial for improving the roundness of the negative electrode active material, increasing its compaction density, reducing capacity loss due to particle breakage, and reducing the material's tortuosity. At the same time, it prevents capacity loss of the negative electrode active material due to excessive coating layer thickness, thereby further improving the energy density of the battery cell.

[0017] In any embodiment, the particle size distribution curve of the negative electrode active material has two characteristic peaks, and the peak position difference between the two characteristic peaks is 4-20 μm.

[0018] The particle size distribution curve of the negative electrode active material exhibits a bimodal characteristic, indicating that the particle size is mainly distributed in two different ranges. Further, by controlling the peak position difference between the two characteristic peaks within the above range, the particle size of the smaller particles is matched with the gap size between the larger particles, thereby improving the filling rate of the particle gaps, thus increasing the compaction density of the negative electrode active material and improving the energy density of the battery cell.

[0019] In any embodiment, the two characteristic peaks include a first characteristic peak and a second characteristic peak, the peak position of the first characteristic peak is smaller than the peak position of the second characteristic peak, and the peak position of the first characteristic peak is 0.5-12μm.

[0020] In some embodiments, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the position of the first characteristic peak is smaller than that of the second characteristic peak, and the position of the second characteristic peak is 6-35 μm.

[0021] The first characteristic peak in the particle size distribution curve of the negative electrode active material is in the range of 0.5-12μm and the second characteristic peak is in the range of 6-35μm. This is beneficial for smaller particles to fill the gaps between larger particles, thereby increasing the compaction density of the negative electrode active material and thus improving the energy density of the battery.

[0022] In any embodiment, the two characteristic peaks include a first characteristic peak and a second characteristic peak, the peak position of the first characteristic peak is smaller than that of the second characteristic peak, and the peak position of the first characteristic peak is 3-10 μm.

[0023] In any embodiment, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the peak position of the first characteristic peak is smaller than that of the second characteristic peak, and the peak position of the second characteristic peak is 14-25 μm.

[0024] The first characteristic peak in the particle size distribution curve of the negative electrode active material is in the range of 3-10 μm and the second characteristic peak is in the range of 14-25 μm, which is conducive to further improving the compaction density of the negative electrode active material and improving the energy density of the battery.

[0025] In any embodiment, the area ratio of the first characteristic peak to the area of ​​the second characteristic peak is 10:90-50:50.

[0026] In any embodiment, the area ratio of the first characteristic peak to the area of ​​the second characteristic peak is 25:75-40:60.

[0027] The area ratio of the first characteristic peak to the second characteristic peak represents the ratio of the number of smaller particles to the number of larger particles. When this ratio is in the range of 10:90-50:50, and further within the range of 25:75-40:60, the smaller particles can fully fill the gaps between the larger particles, while avoiding excessive occupation of non-gap space or increase in side reactions by small particles. This improves the filling rate of the gaps between the larger particles, further increasing the compaction density of the negative electrode active material and improving the energy density and overall performance of the battery.

[0028] In any embodiment, the degree of graphitization of the negative electrode active material is greater than or equal to 88%.

[0029] In any embodiment, the graphitization degree of the negative electrode active material is 90%-96%.

[0030] Graphitization degree reflects the integrity of the graphite crystal structure in a material, that is, the regularity of the arrangement of carbon atoms in the graphite structure. A high degree of graphitization indicates small interlayer spacing, smaller lattice rotation, less random stacking of layers, and a more ordered arrangement, resulting in a higher specific capacity. When the graphitization degree of the negative electrode active material is within the above range, it can effectively improve its specific capacity, which is beneficial for increasing the energy density of the battery cell.

[0031] In any embodiment, the oil absorption value of the negative electrode active material is less than or equal to 65.

[0032] In any embodiment, the oil absorption value of the negative electrode active material is 55-65.

[0033] The oil absorption value of a negative electrode active material is mainly related to its specific surface area, surface properties, particle shape, and particle size distribution. It reflects the material's dispersibility in the negative electrode slurry. A low oil absorption value indicates excellent dispersibility in the negative electrode slurry, resulting in superior anti-settling and dispersibility properties. This facilitates control over the coating weight during electrode coating, leading to the preparation of negative electrode sheets with uniform distribution and thickness of the active material. It also reduces the possibility of uneven local current density during charging and discharging, minimizes lithium plating caused by electrode polarization, and improves battery cycle performance. In conclusion, a suitable range of oil absorption values ​​for the negative electrode active material is beneficial for improving the cycle performance of individual battery cells.

[0034] In any embodiment, the compacted density of the negative electrode active material powder under 2T pressure is 1.5-2 g / cm³. 3.

[0035] In any embodiment, the compacted density of the negative electrode active material powder under 2T pressure is 1.55-1.9 g / cm³. 3 .

[0036] The compaction density of the negative electrode active material powder affects the energy density of the battery. The higher the powder compaction density, the greater the compaction density of the negative electrode film, which is more conducive to increasing the energy density of the battery cell. When the powder compaction density of the negative electrode active material at 2T pressure is within the aforementioned range, it helps to increase the compaction density of the negative electrode film, thereby improving the energy density of the battery cell.

[0037] In any embodiment, the specific capacity of the negative electrode active material is 368-400 mAh / g.

[0038] In any embodiment, the specific capacity of the negative electrode active material is 368-390 mAh / g.

[0039] The specific capacity of the negative electrode active material is closely related to factors such as the properties of microcrystalline graphite and the coating layer, as well as their ratio. By controlling these factors and keeping the specific capacity of the negative electrode active material within the aforementioned range, the energy density, fast-charging performance, and cycle performance of the battery can be effectively improved, thereby optimizing the overall performance of the battery.

[0040] In any embodiment, the compaction density of the negative electrode film layer in the fully discharged state of the battery cell is 1.3 g / cm³. 3 -1.85g / cm 3 .

[0041] In any embodiment, the compaction density of the negative electrode film layer in the fully discharged state of the battery cell is 1.62 g / cm³. 3 -1.8g / cm 3 .

[0042] When a battery cell is fully discharged, the compaction density of the negative electrode film is within the above-mentioned range, which is beneficial to improving the energy density of the battery cell.

[0043] The second aspect of this application provides a method for preparing a negative electrode active material, comprising the following steps: mixing microcrystalline graphite and a coating material and subjecting them to heat treatment to obtain a negative electrode active material; wherein, after heat treatment, the coating material forms a coating layer covering at least a portion of the surface of the microcrystalline graphite, the coating layer comprising amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95.

[0044] The negative electrode active material prepared using the above-described preparation method in this application includes microcrystalline graphite and a coating layer covering at least a portion of the surface of the microcrystalline graphite. The coating layer includes amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95. Microcrystalline graphite is isotropic, and its fine grains are beneficial for increasing the number of end faces where active ions can be embedded in the negative electrode active material, thereby enhancing the fast-charging performance of the battery cell. The roundness of the negative electrode active material, within the range of 0.65-0.95, makes the particle morphology in the negative electrode active material more rounded, reducing bridging between particles and enhancing the slippage between particles under external force, thereby increasing the compaction density of the negative electrode active material. Simultaneously, it reduces the sharp edges of the negative electrode active material, reducing capacity loss caused by particle breakage, thus jointly achieving an increase in battery energy density.

[0045] In any embodiment, the coating material includes at least one of resin and bitumen, wherein the bitumen is selected from petroleum bitumen and bio-bitumen, and the resin is selected from epoxy resin, phenolic resin, coal tar, urea-formaldehyde resin, and furan resin.

[0046] In any embodiment, the coating material includes petroleum bitumen.

[0047] Microcrystalline graphite exhibits high short-range disorder, resulting in excellent kinetic properties that contribute to improved fast-charging performance. However, its surface contains numerous defects, which can easily trigger side reactions. The coating layer formed by heat-treated asphalt is relatively dense, effectively preventing direct contact between the electrolyte and microcrystalline graphite, reducing the occurrence of side reactions, and thus balancing the fast-charging and cycle performance of the battery cells.

[0048] In any embodiment, the maximum temperature for heat treatment is 800°C-1400°C.

[0049] In any embodiment, the maximum temperature for heat treatment is 1200°C-1400°C.

[0050] In this embodiment, the maximum temperature of the heat treatment is further within the range of 1200℃-1400℃, which helps to further improve the energy density and fast charging performance of the battery.

[0051] In any embodiment, mixing microcrystalline graphite and the coating material and then heat-treating them to obtain the negative electrode active material specifically includes: crushing and classifying microcrystalline graphite to obtain first microcrystalline graphite and second microcrystalline graphite; mixing the first microcrystalline graphite, the second microcrystalline graphite, and the coating material and then heat-treating them to obtain the negative electrode active material; wherein, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, the Dv50 of the first microcrystalline graphite is 2-10 μm, optionally 3-8 μm, the Dv99 of the first microcrystalline graphite is 8-30 μm, optionally 12-25 μm; and / or, the Dv50 of the second microcrystalline graphite is 5-30 μm, optionally 10-25 μm; the Dv99 of the second microcrystalline graphite is 28-50 μm, optionally 32-47 μm.

[0052] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the first microcrystalline graphite is 2-10 μm.

[0053] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the first microcrystalline graphite is 3-8 μm.

[0054] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the first microcrystalline graphite is 8-30 μm.

[0055] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the first microcrystalline graphite is 12-25 μm.

[0056] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the second microcrystalline graphite is 5-30 μm.

[0057] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the second microcrystalline graphite is 10-25 μm.

[0058] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the second microcrystalline graphite is 28-50 μm.

[0059] In any embodiment, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the second microcrystalline graphite is 32-47 μm.

[0060] By controlling the Dv50 and Dv99 of the first microcrystalline graphite and / or the second microcrystalline graphite to be within the above range, the size of the first microcrystalline graphite matches the gap size of the second microcrystalline graphite, so that the first microcrystalline graphite can effectively fill the gap of the second microcrystalline graphite, which helps to improve the compaction density of the negative electrode active material, thereby improving the energy density of the battery cell.

[0061] In any embodiment, the mass ratio of the first microcrystalline graphite to the second microcrystalline graphite is 10:90-40:60.

[0062] In any embodiment, the mass ratio of the first microcrystalline graphite to the second microcrystalline graphite is 15:85-30:70.

[0063] Furthermore, in the embodiments of this application, the mass ratio of the first microcrystalline graphite and the second microcrystalline graphite is in the range of 15:85-30:70. The first microcrystalline graphite can fully fill the gaps between the second microcrystalline graphite, while avoiding excessive occupation of non-gap space or increase of side reactions due to excessive first microcrystalline graphite, thereby improving the filling rate of the gaps in the negative electrode active material, increasing the compaction density, and further optimizing the energy density and overall performance of the battery.

[0064] A third aspect of this application provides a battery device comprising a battery cell provided in the first aspect or a negative electrode active material prepared by the preparation method provided in the second aspect.

[0065] The fourth aspect of this application provides an electrical device, which includes the battery device provided in the third aspect, the battery device being used to provide electrical energy.

[0066] The fifth aspect of this application provides an energy storage device, which includes the battery device provided in the third aspect, the battery device being used to store electrical energy.

[0067] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0068] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.

[0069] Figure 1 This is a polished electron microscope image of the cross-section of the negative electrode active material provided in an embodiment of this application;

[0070] Figure 2 This is an electron microscope image of the negative electrode active material provided in an embodiment of this application;

[0071] Figure 3 These are electron microscope images of microcrystalline graphite in the prior art;

[0072] Figure 4 This is a cross-sectional polished electron microscope image of the negative electrode sheet provided in an embodiment of this application;

[0073] Figure 5 These are cross-sectional polished electron microscope images of the negative electrode sheet provided in this application, in proportion to a single scale.

[0074] Figure 6 This is a particle size distribution curve of a negative electrode active material provided in one embodiment and a pair of proportions of this application;

[0075] Figure 7 These are electron microscope (EM) images of graphite, wherein (a) is an EEM image of microcrystalline graphite provided in an embodiment of this application, and (b) is an EEM image of artificial graphite in the prior art.

[0076] Figure 8 This is a schematic diagram of a battery cell provided in some embodiments of this application;

[0077] Figure 9 This is a schematic diagram of a battery module provided in some embodiments of this application;

[0078] Figure 10 This is a schematic diagram of a battery pack provided in some embodiments of this application;

[0079] Figure 11 yes Figure 8 An exploded view of the battery pack shown;

[0080] Figure 12 This is an exploded view of a single battery cell provided in some embodiments of this application;

[0081] Figure 13 This is a schematic diagram of an electrical device provided in some embodiments of this application.

[0082] The accompanying drawings are not necessarily drawn to scale.

[0083] Explanation of reference numerals in the attached drawings: 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Battery module; 5. Battery cell; 51. Casing; 52. Electrode assembly; 53. Cover plate; 6. Negative electrode active material; 61. Core; 62. Coating layer. Detailed Implementation

[0084] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0085] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0086] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0087] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0088] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0089] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0090] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0091] In this application, the terms "multiple" or "various" refer to two or more kinds.

[0092] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0093] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be obtained using various testing methods commonly used in the art.

[0094] The measurements can be performed, for example, according to the test methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.

[0095] The battery mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules, or battery packs.

[0096] A battery cell is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. A battery cell can be cylindrical, cuboid, or other shapes, etc., and the embodiments of this application are not limited in this respect. Figure 8 The example shown is a rectangular battery cell 5.

[0097] When there are multiple battery cells, they are connected in series, parallel, or mixed via a busbar. In some embodiments, the battery can be a battery module; when there are multiple battery cells, they are arranged and fixed to form a battery module. In some embodiments, the battery can be a battery pack, which includes a housing and battery cells, with the battery cells or battery modules housed within the housing. In some embodiments, the housing can be part of the vehicle's chassis structure. For example, a portion of the housing can be at least part of the vehicle's floor, or a portion of the housing can be at least part of the vehicle's crossbeams and longitudinal beams.

[0098] In some embodiments, the battery can be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.

[0099] In some embodiments, individual battery cells can be assembled into a battery module, and the number of individual battery cells contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module. Figure 9 This is a schematic diagram of battery module 4 as an example. Figure 9 As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0100] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0101] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0102] Figure 10 and Figure 11 This is a schematic diagram of battery pack 1 as an example. Figure 10 and Figure 11 As shown, the battery pack 1 may include a housing and multiple battery modules 4 disposed within the housing. The housing includes an upper housing 2 and a lower housing 3. The upper housing 2 covers the lower housing 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the housing.

[0103] The battery provided in this application embodiment may include a lithium-ion battery.

[0104] A single battery cell includes an electrode assembly and an electrolyte. The electrode assembly can be a wound structure or a stacked structure, and the embodiments of this application are not limited in this regard.

[0105] The battery cell may also include an outer packaging, which can be used to encapsulate the electrode components and electrolyte. The outer packaging can be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0106] In some embodiments, such as Figure 12 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. Electrode assemblies 52 are encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, and can be adjusted according to requirements.

[0107] Electrode assemblies typically include positive and negative electrodes. The negative electrode is the electrode that absorbs or lithiates lithium ions during battery charging and releases or delithiates lithium during discharge. The positive electrode is the electrode that releases or delithiates lithium ions during battery charging and absorbs or lithiates lithium during discharge.

[0108] Natural flake graphite and artificial graphite have long-range ordered layered structures and high lithium-ion capacity. Therefore, they are often used as negative electrode active materials for battery cells in existing technologies. However, due to their long-range ordered structure, the insertion speed of lithium ions into the negative electrode active material is limited, making it difficult to further improve the fast charging performance of the battery.

[0109] To address the aforementioned problems, the first aspect of this application provides a battery cell, including a positive electrode, a negative electrode, and an electrolyte; the negative electrode includes a negative current collector and a negative electrode film disposed on at least one side of the negative current collector, the negative electrode film including a negative electrode active material, such as... Figure 1 As shown, the negative electrode active material 6 includes a core 61 and a coating layer 62 that covers at least part of the surface of the core. The core 61 includes microcrystalline graphite, and the coating layer 62 includes amorphous carbon. The roundness of the negative electrode active material 6 is 0.65-0.95.

[0110] According to national standards, microcrystalline graphite refers to an aggregate of natural graphite with a particle size of less than 1 μm. The type of negative electrode active material can be tested using any method known in the art. As an example, scanning electron microscopy is used to observe the cross-section of the negative electrode active material and measure the particle size of the primary particles; graphite with a primary particle size of less than 1 μm is considered microcrystalline graphite. It is worth noting that the negative electrode active material in this application can be either freshly prepared or obtained by scraping powder from a negative electrode sheet.

[0111] Microcrystalline graphite differs from natural flake graphite and artificial graphite (natural flake graphite or artificial graphite has a primary particle size greater than 5 μm), exhibiting an amorphous or cryptocrystalline structure with a relatively disordered layered arrangement. Figure 7 As shown in (a), they are therefore isotropic. The layered arrangement of natural flake graphite and synthetic graphite is ordered, as... Figure 7 As shown in (b), it exhibits anisotropy.

[0112] The core of the negative electrode active material comprises isotropic microcrystalline graphite with fine grains, which helps increase the number of intercalation faces for active ions within the negative electrode active material, thereby enhancing the fast-charging performance of the battery cell. However, the irregular shape of the microcrystalline graphite results in a lower compaction density, such as... Figure 3 and Figure 5 As shown, it is prone to breakage under the action of external force or internal stress, resulting in capacity decay and low energy density of the battery cell.

[0113] This application utilizes amorphous carbon to coat microcrystalline graphite and controls the roundness of the negative electrode active material within the range of 0.65-0.95, resulting in a more rounded particle morphology in the negative electrode active material. Figure 2 As shown, reducing bridging between particles enhances the slippage between particles under external force, thereby increasing the compaction density of the negative electrode active material. Figure 4 As shown, this reduces the sharp edges of the negative electrode active material, thereby reducing capacity loss caused by particle breakage and thus improving the battery energy density. At the same time, the amorphous carbon coating maintains the kinetic advantages of microcrystalline graphite.

[0114] Amorphous carbon refers to carbon materials with a very low degree of graphitization, exhibiting an approximately amorphous morphology (or lacking a fixed shape and periodic structural regularity). The carbon atoms in amorphous carbon structures are not arranged in a regular pattern; therefore, amorphous carbon can be characterized by TEM (Transient Electron Microscopy). By using a focused ion beam (FIB) to cut a thin slice approximately 100 nm thick from the middle of the negative electrode active material particles, and then performing TEM on the slice, it can be observed that the surface region includes a coating layer. The lattice fringes in the coating layer exhibit long-range disorder and short-range order, and the electron diffraction pattern shows a halo-like appearance, indicating that the coating layer contains amorphous carbon.

[0115] In this document, the roundness of the negative electrode active material refers to the ratio of the shortest inner diameter R1 to the longest inner diameter R2 of the particles in the negative electrode active material, which can be obtained by methods and instruments known in the art. As an example, specifically, a prepared negative electrode sheet, or a negative electrode sheet disassembled from a battery, is taken and subjected to CP-SEM testing. A number of points are randomly selected for imaging, with the number of points being ≥10 (e.g., 10, 20, 50, 100, etc.). The particles in the captured images are identified using AVIZO software, and the longest inner diameter, shortest inner diameter, and area of ​​the particles are measured. Roundness = R1 / R2. In some embodiments, the roundness of the negative electrode active material can be selected as 0.65, 0.7, 0.73, 0.75, 0.77, 0.8, 0.85, 0.9, 0.95, or any value range between the two.

[0116] In some embodiments, the roundness of the negative electrode active material is 0.75-0.9.

[0117] Controlling the roundness of the negative electrode active material within the range of 0.75-0.9 helps to further reduce capacity loss caused by particle breakage while maintaining the high compaction density of the negative electrode active material, thereby increasing the compaction density and specific capacity of the negative electrode active material and thus improving the energy density of the battery. On the other hand, it helps to improve the tortuosity of the negative electrode film and improve the dynamic performance of the electrode, thereby further improving the fast charging performance of the battery.

[0118] In some embodiments, the R value of the negative electrode active material is 88%-96%, where R = 1. G / (I G +I D ), I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.

[0119] In some embodiments, the R value of the negative electrode active material is 88%-92%, where R = 1. G / (I G +I D ), I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.

[0120] When used in this article, the formula for calculating the R value is R = I G / (I G +I D), where I G This refers to the peak height of the G-band in the Raman spectrum. D This refers to the height of the D-band peak; the G-band peak is located at 1585±50cm. -1 The position of peak D is 1350±50cm. -1 .

[0121] The R-value of the negative electrode active material can be obtained using a laser confocal Raman spectrometer in surface scanning mode. An example is as follows: Using a laser confocal Raman spectrometer (e.g., a high-precision Renishaw laser confocal Raman spectrometer), a laser wavelength of 532 nm is selected. An appropriate amount of sample is taken and its surface is scanned in all directions. The scanning area is 100 μm × 100 μm, the step size is 2 μm, and the total number of scanning points is 2500. The R-values ​​at different sites are obtained, and the average of the 2500 R-values ​​is the R-value of the negative electrode active material.

[0122] In some embodiments, the R value of the negative electrode active material can be selected as 88%, 88.2%, 88.5%, 89%, 89.5%, 90%, 90.3%, 90.4%, 90.5%, 91%, 91.2%, 91.5%, 92%, 92.5%, 93%, 93.5%, 93.7%, 94%, 94.5%, 95%, 95.5%, 96%, or any range between the two.

[0123] The R-value characterizes the degree of defect and disorder in the negative electrode active material. The smaller the value, the greater the degree of surface defect and the higher the surface disorder of the negative electrode active material. When the R-value of the negative electrode active material is within the above range, the amorphous carbon in the coating layer has a high degree of disorder, which is beneficial to increasing the transport path of active ions and improving the insertion and extraction rate of active ions in the negative electrode active material, thereby improving the fast charging performance of the battery.

[0124] In some embodiments, the orientation degree (OI) of the negative electrode active material is 0.5-4.

[0125] In some embodiments, the orientation degree (OI) of the negative electrode active material is 1.5-3.

[0126] In this document, the orientation degree (OI) value has a well-known meaning in the art, representing the degree of order in the arrangement of crystals or particles in a material. It can be determined using an orientation degree meter or an X-ray diffractometer, as illustrated below: Using an X-ray diffractometer (such as a Bruker D8 Discover), the test can be performed according to JISK0131-1996 and JB / T 4220-2011. The X-ray diffraction pattern of the material is obtained, and the OI value is calculated using the formula OI value = I004 / I110. I004 is the integrated area of ​​the diffraction peak of the 004 crystal plane of crystalline carbon in the material, and I110 is the integrated area of ​​the diffraction peak of the 110 crystal plane of crystalline carbon in the material. In the X-ray diffraction analysis test of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the wavelength of the rays is... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min.

[0127] In some embodiments, the orientation degree (OI) value of the negative electrode active material can be selected as 0.5, 1, 1.5, 2, 2.5, 2.8, 3, 3.2, 3.5, 4, or any value range between the two.

[0128] The OI value reflects the disorder of the material. The OI value of the negative electrode active material within the above range shows a strong degree of disorder, that is, the negative electrode active material is isotropic, the fine crystals inside the material are randomly packed, the number of end faces where active ions can be inserted is large, and the insertion speed is improved, which helps to improve the fast charging performance of the battery cell.

[0129] In some embodiments, the thickness of the coating layer is 1-300 nm, optionally 5-200 nm.

[0130] The thickness of the coating layer can be measured using methods known in the art; for example, it can be obtained through transmission electron microscopy (TEM). A thin slice of approximately 20-50 nm thickness is cut from the bulk of the negative electrode active material particle using focused ion beam (FIB), and then TEM is performed on the slice to obtain the raw TEM image. The raw TEM image is opened in Digital Micrograph software, and the disordered layer is identified by diffraction fringes or lattice spacing, and its thickness is measured. Typically, the coating layer does not have diffraction fringes, and the lattice spacing is larger than that of the core.

[0131] In some embodiments, the thickness of the coating layer can be selected as 1 nm, 5 nm, 20 nm, 50 nm, 100 nm, 150 nm, 170 nm, 200 nm, 250 nm, 300 nm or any value range between the two.

[0132] Within the aforementioned range, the thickness of the coating layer is beneficial for improving the roundness of the negative electrode active material, increasing its compaction density, reducing capacity loss due to particle breakage, and reducing the material's tortuosity. At the same time, it prevents capacity loss of the negative electrode active material due to excessive coating layer thickness, thereby further improving the energy density of the battery cell.

[0133] In some embodiments, the particle size distribution curve of the negative electrode active material has two characteristic peaks, such as... Figure 6 As shown, the peak position difference between the two characteristic peaks is 4-20 μm.

[0134] The particle size distribution curve of the negative electrode active material can be determined using instruments and methods known in the art. For example, it can be conveniently determined using a laser particle size analyzer, referring to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0135] In this paper, the peak position of the characteristic peak is the x-coordinate value corresponding to the characteristic peak.

[0136] In some embodiments, the particle size distribution curve of the negative electrode active material has two characteristic peaks, and the peak position difference between the two characteristic peaks can be selected as 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value range between the two.

[0137] The particle size distribution curve of the negative electrode active material exhibits a bimodal characteristic, indicating that the particle size is mainly distributed in two different ranges. Further, by controlling the peak position difference between the two characteristic peaks within the above range, the particle size of the smaller particles is matched with the gap size between the larger particles, thereby improving the filling rate of the particle gaps, thus increasing the compaction density of the negative electrode active material and improving the energy density of the battery cell.

[0138] In some embodiments, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the peak position of the first characteristic peak is smaller than that of the second characteristic peak, and the peak position of the first characteristic peak is 0.5-12 μm.

[0139] In some embodiments, the first characteristic peak position is a numerical range of 0.5μm, 1μm, 2μm, 3μm, 3.8μm, 4μm, 4.3μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or any two of these values.

[0140] In some embodiments, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the position of the first characteristic peak is smaller than that of the second characteristic peak, and the position of the second characteristic peak is 6-35 μm.

[0141] The first characteristic peak is the characteristic peak with a smaller abscissa value in the particle size distribution curve of the negative electrode active material, and the second characteristic peak is the characteristic peak with a larger abscissa value.

[0142] In some embodiments, the second characteristic peak position is a numerical range of 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 13μm, 14μm, 15μm, 18μm, 20μm, 22μm, 25μm, 30μm, 35μm or any two of these values.

[0143] In this embodiment, the first characteristic peak in the particle size distribution curve of the negative electrode active material is in the range of 0.5-12μm and the second characteristic peak is in the range of 6-35μm. This is beneficial for smaller particles to fill the gaps between larger particles, thereby increasing the compaction density of the negative electrode active material and thus improving the energy density of the battery.

[0144] In some embodiments, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the position of the first characteristic peak is smaller than that of the second characteristic peak, and the position of the first characteristic peak is 3-10 μm.

[0145] In some embodiments, the two characteristic peaks include a first characteristic peak and a second characteristic peak, wherein the position of the first characteristic peak is smaller than that of the second characteristic peak, and the position of the second characteristic peak is 14-25 μm.

[0146] Furthermore, in the embodiments of this application, the first characteristic peak in the particle size distribution curve of the negative electrode active material is in the range of 3-10 μm and the second characteristic peak is in the range of 14-25 μm, which is beneficial to further improve the compaction density of the negative electrode active material and improve the energy density of the battery.

[0147] In some embodiments, the area ratio of the first characteristic peak to the area of ​​the second characteristic peak is 10:90-50:50.

[0148] In some embodiments, the area ratio of the first characteristic peak to the area of ​​the second characteristic peak is 25:75-40:60.

[0149] In some embodiments, the area ratio of the first characteristic peak to the area of ​​the second characteristic peak can be selected as 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50 or any range between the two.

[0150] When used in this paper, the ratio of the area of ​​the first characteristic peak to the area of ​​the second characteristic peak refers to the ratio of the peak areas in the particle size distribution curve obtained directly by using a laser particle size analyzer according to the laser diffraction method for particle size distribution in GB / T19077-2016.

[0151] The area ratio of the first characteristic peak to the second characteristic peak represents the ratio of the number of smaller particles to the number of larger particles. When this ratio is in the range of 10:90-50:50, and further within the range of 25:75-40:60, the smaller particles can fully fill the gaps between the larger particles, while avoiding excessive occupation of non-gap space or increase in side reactions by small particles. This improves the filling rate of the gaps between the larger particles, further increasing the compaction density of the negative electrode active material and improving the energy density and overall performance of the battery.

[0152] In some embodiments, the graphitization degree of the negative electrode active material is greater than or equal to 88%.

[0153] In some embodiments, the graphitization degree of the negative electrode active material is 90%-96%.

[0154] In some embodiments, the degree of graphitization of the negative electrode active material can be selected as 88%, 88.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, or any value range between the two.

[0155] In this document, the degree of graphitization of the negative electrode active material has a meaning known in the art and can be tested using instruments and methods known in the art. For example, it can be tested using an X-ray diffractometer (such as a Bruker D8 Discover), and the testing can be performed with reference to JISK 0131-1996 and JB / T 4220-2011. The average interlayer spacing d002 of the C(002) crystal plane in the material's crystal structure is obtained, and then the degree of graphitization is calculated according to the formula g = (0.344 - d002) / (0.344 - 0.3354) × 100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure, expressed in nanometers (nm).

[0156] Graphitization degree reflects the integrity of the graphite crystal structure in a material, that is, the regularity of the arrangement of carbon atoms in the graphite structure. A high degree of graphitization indicates small interlayer spacing, smaller lattice rotation, less random stacking of layers, and a more ordered arrangement, resulting in a higher specific capacity. When the graphitization degree of the negative electrode active material is within the above range, it can effectively improve its specific capacity, which is beneficial for increasing the energy density of the battery cell.

[0157] In some embodiments, the oil absorption value of the negative electrode active material is less than or equal to 65.

[0158] In some embodiments, the oil absorption value of the negative electrode active material is 55-65.

[0159] In some embodiments, the oil absorption value of the negative electrode active material can be selected as 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65 or any range between the two.

[0160] In this article, the term "oil absorption value" refers to the volume of linseed oil that 100g of negative electrode active material can absorb. For example, an oil absorption value of 60ml / 100g for negative electrode active material means that 100g of negative electrode active material can absorb 60ml of linseed oil.

[0161] The oil absorption value of the negative electrode active material can be tested using methods and equipment known in the art, as illustrated below: Test oil and a negative electrode active material sample are obtained separately, and the torque threshold of the oil absorption value tester is set. Oil is added at a constant rate to the sample in the mixing chamber of the oil absorption value tester. As the amount of oil absorbed by the sample increases, the viscosity of the mixture between the sample and the oil continuously increases. When the viscosity of the mixture reaches the preset torque threshold of the oil absorption value tester, the test is stopped, and the volume of oil absorbed per unit mass of sample is calculated. This value is the oil absorption value QI of the sample. The test oil is linseed oil (DBP), and the torque threshold is 1 N.

[0162] The oil absorption value of a negative electrode active material is mainly related to its specific surface area, surface properties, particle shape, and particle size distribution. It reflects the material's dispersibility in the negative electrode slurry. A low oil absorption value indicates excellent dispersibility in the negative electrode slurry, resulting in superior anti-settling and dispersibility properties. This facilitates control over the coating weight during electrode coating, leading to the preparation of negative electrode sheets with uniform distribution and thickness of the active material. It also reduces the possibility of uneven local current density during charging and discharging, minimizes lithium plating caused by electrode polarization, and improves battery cycle performance. In conclusion, a suitable range of oil absorption values ​​for the negative electrode active material is beneficial for improving the cycle performance of individual battery cells.

[0163] In some embodiments, the compaction density of the negative electrode active material powder under 2T pressure is 1.5-2 g / cm³. 3 .

[0164] In some embodiments, the compacted density of the negative electrode active material powder under 2T pressure is 1.55-1.9 g / cm³. 3 .

[0165] In some embodiments, the powder compaction density of the negative electrode active material under 2T pressure can be selected as 1.5 g / cm³.3 1.6g / cm 3 1.62g / cm 3 1.65g / cm 3 1.68g / cm 3 1.7g / cm 3 1.75g / cm 3 1.77g / cm 3 1.8g / cm 3 1.9g / cm 3 2g / cm 3 Or the range of values ​​between any two.

[0166] In this paper, the term "powder compaction density" refers to the density of the powder to be tested under a preset pressure.

[0167] The method for measuring the compacted density of powder can be any method known in the art. For example, referring to GB / T24533-2009, 1g of negative electrode active material powder is weighed and added to a container with a bottom area of ​​1.327cm². 2 In the mold, pressure is applied to a specific pressure, such as 2T, held for 30s, then depressurized and held for 10s. The compaction density of the negative electrode active material under the selected pressure is determined by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0168] The compaction density of the negative electrode active material powder affects the energy density of the battery. The higher the powder compaction density, the greater the compaction density of the negative electrode film, which is more conducive to increasing the energy density of the battery cell. When the powder compaction density of the negative electrode active material at 2T pressure is within the aforementioned range, it helps to increase the compaction density of the negative electrode film, thereby improving the energy density of the battery cell.

[0169] In some embodiments, the specific capacity of the negative electrode active material is 368-400 mAh / g.

[0170] In some embodiments, the specific capacity of the negative electrode active material is 368-390 mAh / g.

[0171] In some embodiments, the specific capacity of the negative electrode active material can be selected as 368mAh / g, 370mAh / g, 371mAh / g, 373mAh / g, 375mAh / g, 376mAh / g, 376.5mAh / g, 377mAh / g, 380mAh / g, 390mAh / g, 400mAh / g, or any value range between the two.

[0172] The specific capacity can be measured using methods and instruments known in the art. For example, the negative electrode active material, binder (polyvinyl alcohol), and conductive agent (SP-Li) can be thoroughly mixed in a suitable amount of deionized water at a weight ratio of 90:5:5 to form a uniform negative electrode slurry. The negative electrode slurry is then uniformly coated onto the surface of the negative electrode current collector copper foil and dried and cold-pressed. Subsequently, using a lithium metal sheet as the counter electrode and a polyethylene film as the separator, an electrolyte is injected. The electrolyte formulation is as follows: ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed uniformly at a volume ratio of 1:1:1. A certain amount of LiPF6 lithium salt is dissolved in the organic solvent, controlling the lithium salt concentration to 1 mol / L, and stirred uniformly to obtain the electrolyte. A CR2430 coin cell is then assembled in an argon-protected glove box. At 25°C, the prepared coin cell was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and allowed to stand for 5 minutes. The first discharge capacity of the coin cell was recorded. Subsequently, it was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the coin cell was recorded. The ratio of the charging capacity of the coin cell to the mass of the negative electrode active material sample is the specific capacity of the negative electrode active material.

[0173] The specific capacity of the negative electrode active material is closely related to factors such as the properties of microcrystalline graphite and the coating layer, as well as their ratio. By controlling these factors and keeping the specific capacity of the negative electrode active material within the aforementioned range, the energy density, fast-charging performance, and cycle performance of the battery can be effectively improved, thereby optimizing the overall performance of the battery.

[0174] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of the battery cell is 1.3 g / cm³. 3 -1.85g / cm 3 .

[0175] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of the battery cell is 1.62 g / cm³. 3 -1.8g / cm 3 .

[0176] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of the battery cell can be selected as 1.3 g / cm³. 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.62g / cm 3 1.65g / cm 3 1.68g / cm 3 1.7g / cm 3 1.75g / cm3 1.77g / cm 3 1.8g / cm 3 Or the range of values ​​between any two.

[0177] In this application, the fully discharged state refers to the state after the battery is placed in a 25°C oven environment, left to stand for 2 hours, and the battery temperature is maintained at 25°C, and then discharged at a constant current of 1 / 3C to 2.8V and then discharged at a constant current of 0.1C to 2.8V.

[0178] The compaction density of the negative electrode film can be tested using methods known in the art. As an example, disassemble a battery in a fully discharged state, clean the negative electrode sheet three times or more with a solvent such as dimethyl carbonate (DMC), and dry it. Weigh a negative electrode sample with an area of ​​S using an electronic balance, denoted as W1, and measure the thickness T1 of the negative electrode sheet using a micrometer. Then wipe off the weighed electrode film, weigh the negative current collector, denoted as W2, and measure the thickness T2 of the negative current collector using a micrometer. The compaction density of the negative electrode film is then calculated as PD = (W1 - W2) / [(T1 - T2) × S].

[0179] When a battery cell is fully discharged, the compaction density of the negative electrode film is within the above-mentioned range, which is beneficial to improving the energy density of the battery cell.

[0180] This application also provides a method for preparing a negative electrode active material, comprising the following steps: mixing microcrystalline graphite and a coating material and subjecting them to heat treatment to obtain a negative electrode active material; wherein, after heat treatment, the coating material forms a coating layer covering at least a portion of the surface of the microcrystalline graphite, the coating layer comprising amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95.

[0181] The negative electrode active material prepared using the above-described preparation method in this application includes microcrystalline graphite and a coating layer covering at least a portion of the surface of the microcrystalline graphite. The coating layer includes amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.95. Microcrystalline graphite is isotropic, and its fine grains are beneficial for increasing the number of end faces where active ions can be embedded in the negative electrode active material, thereby enhancing the fast-charging performance of the battery cell. The roundness of the negative electrode active material, within the range of 0.65-0.95, makes the particle morphology in the negative electrode active material more rounded, reducing bridging between particles and enhancing the slippage between particles under external force, thereby increasing the compaction density of the negative electrode active material. Simultaneously, it reduces the sharp edges of the negative electrode active material, reducing capacity loss caused by particle breakage, thus jointly achieving an increase in battery energy density.

[0182] In some embodiments, the coating material includes at least one of resin and bitumen, wherein the bitumen is selected from petroleum bitumen and bio-bitumen, and the resin is selected from epoxy resin, phenolic resin, coal tar, urea-formaldehyde resin, and furan resin.

[0183] Microcrystalline graphite exhibits high short-range disorder, resulting in excellent kinetic properties that contribute to improved fast-charging performance. However, its surface contains numerous defects, which can easily trigger side reactions. Coating it can prevent direct contact between the electrolyte and microcrystalline graphite, reducing the occurrence of side reactions and thus balancing the fast-charging and cycle performance of individual battery cells.

[0184] However, during the battery charging and discharging process, the coating layer formed after resin heat treatment is prone to powder shedding, which in turn affects the battery's cycle performance.

[0185] In some embodiments, the coating material includes bitumen, which is selected from petroleum bitumen and bio-bitumen.

[0186] In some embodiments, the coating material includes petroleum bitumen.

[0187] The coating layer formed by heat treatment of asphalt is relatively dense, which can effectively block the direct contact between the electrolyte and microcrystalline graphite, further reducing the occurrence of side reactions, thereby balancing the fast charging performance and cycle performance of the battery cell.

[0188] In some embodiments, the maximum temperature for heat treatment is 800°C-1400°C.

[0189] In some embodiments, the maximum temperature for heat treatment can be selected as 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, or any range between the two.

[0190] If the maximum temperature of the coating heat treatment is too high, the coating material is prone to pulverization and cannot improve the roundness. In this embodiment, the maximum temperature of the coating heat treatment is within the aforementioned range. After heat treatment within this temperature range, the asphalt forms amorphous carbon, and the negative electrode active material has a suitable R value, which is beneficial for increasing the transport path of active ions and improving the insertion / extraction rate of active ions in the negative electrode active material, thereby further improving the fast-charging performance of the battery. Simultaneously, the amorphous coating layer gives the negative electrode active material a higher roundness, which helps to increase the compaction density of the negative electrode active material, thereby further improving the energy density of the battery.

[0191] In some embodiments, the maximum temperature for heat treatment is 1200°C-1400°C.

[0192] In this embodiment, the maximum temperature of the heat treatment is further within the range of 1200℃-1400℃, which helps to further improve the energy density and fast charging performance of the battery.

[0193] In some embodiments, mixing microcrystalline graphite and a coating material and then heat-treating them to obtain a negative electrode active material specifically includes: crushing and classifying microcrystalline graphite to obtain a first microcrystalline graphite and a second microcrystalline graphite; mixing the first microcrystalline graphite, the second microcrystalline graphite, and the coating material and then heat-treating them to obtain the negative electrode active material; wherein, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, the Dv50 of the first microcrystalline graphite is 2-10 μm, optionally 3-8 μm, the Dv99 of the first microcrystalline graphite is 8-30 μm, optionally 12-25 μm; and / or, the Dv50 of the second microcrystalline graphite is 5-30 μm, optionally 10-25 μm; the Dv99 of the second microcrystalline graphite is 28-50 μm, optionally 32-47 μm.

[0194] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the first microcrystalline graphite is 2-10 μm.

[0195] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the first microcrystalline graphite is 3-8 μm.

[0196] In some embodiments, the Dv50 of the first microcrystalline graphite can be selected as 2μm, 3μm, 3.8μm, 4μm, 4.3μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any value range between the two.

[0197] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the first microcrystalline graphite is 8-30 μm.

[0198] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the first microcrystalline graphite is 12-25 μm.

[0199] In some embodiments, the Dv99 of the first microcrystalline graphite can be selected as 8μm, 9μm, 10μm, 12μm, 15μm, 17μm, 18μm, 19μm, 20μm, 25μm, 30μm or any value range between the two.

[0200] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the second microcrystalline graphite is 5-30 μm.

[0201] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv50 of the second microcrystalline graphite is 10-25 μm.

[0202] In some embodiments, the Dv50 of the second microcrystalline graphite can be selected as 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 13μm, 14μm, 15μm, 16μm, 18μm, 20μm, 25μm, 30μm or any value range between the two.

[0203] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the second microcrystalline graphite is 28-50 μm.

[0204] In some embodiments, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, and the Dv99 of the second microcrystalline graphite is 32-47 μm.

[0205] In some embodiments, the Dv50 of the second microcrystalline graphite can be selected as 28μm, 30μm, 32μm, 34μm, 35μm, 37μm, 39μm, 40μm, 45μm, 47μm, 50μm or any value range between the two.

[0206] Dv50 and Dv99 are well-known terms in the art, representing the particle size corresponding to a cumulative volumetric distribution percentage of 50% and 99%, respectively, and can be determined using instruments and methods known in the art. For example, they can be conveniently determined using a laser particle size analyzer, referring to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0207] By controlling the Dv50 and Dv99 of the first microcrystalline graphite and / or the second microcrystalline graphite to be within the above range, the size of the first microcrystalline graphite matches the gap size of the second microcrystalline graphite, so that the first microcrystalline graphite can effectively fill the gap of the second microcrystalline graphite, which helps to improve the compaction density of the negative electrode active material, thereby improving the energy density of the battery cell.

[0208] In some embodiments, the mass ratio of the first microcrystalline graphite to the second microcrystalline graphite is 10:90-40:60.

[0209] In some embodiments, the mass ratio of the first particle and the second particle can be selected as 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60 or any range between the two.

[0210] In some embodiments, the mass ratio of the first microcrystalline graphite to the second microcrystalline graphite is 15:85-30:70.

[0211] Furthermore, in the embodiments of this application, the mass ratio of the first microcrystalline graphite and the second microcrystalline graphite is in the range of 15:85-30:70. The first microcrystalline graphite can fully fill the gaps between the second microcrystalline graphite, while avoiding excessive occupation of non-gap space or increase of side reactions due to excessive first microcrystalline graphite, thereby improving the filling rate of the gaps in the negative electrode active material, increasing the compaction density, and further optimizing the energy density and overall performance of the battery.

[0212] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0213] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0214] Battery device

[0215] This application also provides a battery device, which includes a battery cell provided in this application or a negative electrode active material prepared by the preparation method provided in this application.

[0216] Battery devices include one or more of the following: battery modules, battery packs, and energy storage batteries.

[0217] Electrical appliances

[0218] This application also provides an electrical device, which includes a battery device provided in this application embodiment. The battery device is used to provide electrical energy. The battery can be used as the power source for the electrical device. The electrical device can be, but is not limited to, mobile devices (such as mobile phones, tablets, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, and satellites.

[0219] Electrical devices can choose the specific type of battery according to their usage needs, such as individual battery cells, battery modules, or battery packs.

[0220] Figure 13 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0221] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0222] Energy storage devices

[0223] This application also provides an energy storage device, which includes the battery device provided in this application embodiment. The battery device is used to store electrical energy. The battery device can be used as an energy storage unit of the energy storage device. The energy storage unit can be, but is not limited to, an energy storage container, an energy storage cabinet, an energy storage power station, an energy storage battery pack, or a portable energy storage system, etc.

[0224] Example

[0225] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0226] I. Preparation Method

[0227] Example 1

[0228] (1) Preparation of negative electrode sheet

[0229] Preparation of negative electrode active materials:

[0230] S1: The negative electrode active material raw material (microcrystalline graphite with an OI value of 2.6) is crushed, sieved and classified to obtain the first microcrystalline graphite with Dv50 of 4μm and Dv99 of 18μm and the second microcrystalline graphite with Dv50 of 15μm and Dv99 of 37μm.

[0231] S2: Mix the first microcrystalline graphite, the second microcrystalline graphite, and solid petroleum asphalt evenly at a mass ratio of 25:75:2.5, and then place them in a horizontal reactor for heating and carbonization. During heating, a stepped heating and heat preservation process is adopted. The programmed heating platforms are set to 200℃, 300℃, 500℃, and 1200℃, respectively. The temperature is maintained at 200℃ for 2 hours, 300℃ for 2 hours, 500℃ for 4 hours, and 1200℃ for 4 hours. After cooling for 8 hours, the negative electrode active material is obtained.

[0232] The anode active material exhibits an orientation index (OI) of 2.8, a graphitization degree of 96%, and an oil absorption value of 57. The coating thickness is 170 nm. Under 2T pressure, the powder compaction density of the anode active material is 1.65 g / cm³. 3 .

[0233] Preparation of negative electrode film:

[0234] The prepared negative electrode active material, binder (polyvinyl alcohol), and conductive agent (SP-Li) are dissolved in deionized water at a weight ratio of 90:5:5. After thorough ball milling and uniform mixing, a negative electrode slurry is prepared. The negative electrode slurry is then uniformly coated onto the negative electrode current collector once or multiple times. After drying, a negative electrode film is obtained, which is then cold-pressed and slit to obtain a negative electrode sheet.

[0235] (2) Preparation of positive electrode sheet

[0236] The positive electrode active material (LiNi) 0.9 Co 0.05 Mn 0.05 O2), conductive super carbon black, and polyvinylidene fluoride (PVDF) are dissolved in NMP (N-methylpyrrolidone) solvent at a mass ratio of 93:5:1. The mixture is thoroughly stirred and mixed evenly, and then wetted, kneaded and dispersed to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector, and then dried, cold-pressed and cut to obtain the positive electrode sheet.

[0237] (3) Preparation of electrolyte

[0238] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), organic solvents ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed evenly in a volume ratio of 1:1:1. A certain amount of lithium LiPF6 salt is dissolved in the organic solvent, and the concentration of lithium salt is controlled at 1 mol / L. The mixture is stirred evenly to obtain the electrolyte.

[0239] (4) Separating membrane

[0240] A polyethylene film with a thickness of 13 μm.

[0241] (5) Battery manufacturing

[0242] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrodes are then wound to obtain the electrode assembly. The electrode assembly is placed in a battery casing, dried, and then injected with the electrolyte. Following formation and settling processes, a lithium-ion battery is produced.

[0243] Example 2

[0244] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the amount of solid petroleum asphalt added in step S2 is adjusted. Specifically, the mass ratio of the first microcrystalline graphite, the second microcrystalline graphite and the solid petroleum asphalt is 25:75:2, as detailed in Table 1.

[0245] Example 3

[0246] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the amount of solid petroleum asphalt added in step S2 is adjusted. Specifically, the mass ratio of the first microcrystalline graphite, the second microcrystalline graphite and the solid petroleum asphalt is 25:75:1.7, as detailed in Table 1.

[0247] Examples 4-5

[0248] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the temperature setting of the programmed temperature rise platform in step S2 is adjusted. Specifically, the programmed temperature rise platform in Example 4 is set to 200℃, 300℃, 500℃, and 1000℃, with constant temperatures of 200℃ for 2 hours, 300℃ for 2 hours, 500℃ for 4 hours, and 1000℃ for 4 hours; the programmed temperature rise platform in Example 5 is set to 200℃, 300℃, 500℃, and 1400℃, with constant temperatures of 200℃ for 2 hours, 300℃ for 2 hours, 500℃ for 4 hours, and 1400℃ for 4 hours, as detailed in Table 1.

[0249] Example 6

[0250] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the raw materials of the negative electrode active material are adjusted. Specifically, microcrystalline graphite with an OI value of 3.37 is selected as the negative electrode active material, so that the orientation degree OI value of the prepared negative electrode active material is 3.5, as detailed in Table 1.

[0251] Example 7

[0252] The preparation method of the lithium-ion battery is similar to that of Example 1. The difference is that the sieve mesh used for sieving and classifying the obtained particles in step S1 is adjusted so that the Dv50 of the first microcrystalline graphite is 4μm and the Dv99 is 18μm, and the Dv50 of the second microcrystalline graphite is 13μm and the Dv99 is 34μm, as detailed in Table 1.

[0253] Example 8

[0254] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the sieve mesh used for sieving and classifying the obtained particles in step S1 is adjusted so that the Dv50 of the first microcrystalline graphite is 2μm and the Dv99 is 9μm, and the Dv50 of the second microcrystalline graphite is 7μm and the Dv99 is 28μm, as detailed in Table 1.

[0255] Examples 9-10

[0256] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the mass ratio of the first microcrystalline graphite and the second microcrystalline graphite in step S2 is adjusted. Specifically, in Example 9, the mass ratio of the first microcrystalline graphite, the second microcrystalline graphite, and the solid petroleum asphalt is 40:60:2.5; in Example 10, the mass ratio of the first microcrystalline graphite, the second microcrystalline graphite, and the solid petroleum asphalt is 14:84:2.5, as detailed in Table 1.

[0257] Example 11

[0258] The preparation method of the lithium-ion battery is similar to that of Example 1, except that it does not contain the first particle, as detailed in Table 1.

[0259] Comparative Example 1

[0260] The preparation method of the lithium-ion battery is similar to that in Example 1, except that the preparation steps of the negative electrode active material are adjusted. The specific steps for preparing the negative electrode active material are as follows: the microcrystalline graphite raw material for the negative electrode active material is crushed, sieved and classified to directly obtain a negative electrode active material with a Dv50 of 13.8 μm and a Dv99 of 35.7 μm, as detailed in Table 1.

[0261] Comparative Example 2

[0262] The preparation method of the lithium-ion battery is similar to that of Example 11, except that the temperature setting of the programmed temperature rise platform in step S2 is adjusted. Specifically, the programmed temperature rise platform of Comparative Example 2 is set to 200℃, 300℃, 500℃, and 2800℃, respectively, and held at 200℃ for 2 hours, 300℃ for 2 hours, 500℃ for 4 hours, and 2800℃ for 4 hours, as detailed in Table 1.

[0263] Comparative Example 3

[0264] The preparation method of the lithium-ion battery is similar to that of Example 11, except that the types of raw materials for the negative electrode active material are adjusted. Specifically, the natural flake graphite raw material for the negative electrode active material is crushed, sieved and graded to obtain first natural flake graphite with Dv50 of 4μm and Dv99 of 18μm and second natural flake graphite with Dv50 of 15μm and Dv99 of 37μm. The first natural flake graphite, the second natural flake graphite and solid petroleum asphalt are mixed evenly at a mass ratio of 25:75:2.5, and then placed in a horizontal reactor for heating and carbonization. A stepped heating and holding process is adopted during heating. The programmed heating platform is set to 200℃, 300℃, 500℃ and 1200℃, respectively. The temperature is held at 200℃ for 2h, 300℃ for 2h, 500℃ for 4h and 1200℃ for 4h. After cooling for 8h, the material is removed from the furnace to obtain the negative electrode active material, as detailed in Table 1.

[0265] II. Performance Testing

[0266] 1. Battery volumetric energy density test:

[0267] The lithium-ion secondary battery was left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. At 25°C, the battery was charged at 0.33C to the charging cutoff voltage of 4.25V, and then continued constant-voltage charging at this voltage until the current reached 0.05C, at which point charging was stopped (where C represents the rated capacity of the lithium-ion secondary battery). After leaving the battery to stand at 25°C for 1 hour, it was discharged at 0.33C to the discharge cutoff voltage of 2.8V at 25°C. The total discharge energy was recorded as E0. The length, width, and height of the lithium-ion secondary battery were measured, and the volume V0 was calculated as V0 = length * width * height. The volumetric energy density of the lithium-ion secondary battery = discharge energy E0 / volume V0.

[0268] 2. Battery fast charging performance test (charging time test):

[0269] ① Voltage calibration: 1) The positive electrode, negative electrode, separator, and electrolyte in the example or comparative example are used to prepare a stacked three-electrode battery, and it is placed at 25°C for 30 min; 2) At 25°C, the battery cells are charged at 0.33C to the charging cutoff voltage of 4.25V, and then constant voltage charging is continued at the charging cutoff voltage until the current is 0.05C, and the charging is cut off (where C represents the rated capacity of the battery cell); 3) Place it at 25°C for 1 h; 4) At 25°C, the battery cells are discharged at 0.33C to the discharge cutoff voltage of 2.8V, and the total discharge capacity C0 of the battery cells is recorded; 5) Place it at 25°C for 1 h.

[0270] ② Room temperature charging test: 1) Prepare a stacked three-electrode battery using the positive electrode, negative electrode, separator, and electrolyte from the examples or comparative examples, and let it stand for 30 minutes; 2) Discharge with 0.33C0 DC to the discharge cutoff voltage of 2.8V, at which point the SOC is 0%; 3) Let it stand for 5 minutes; 4) Charge with 5C0 constant current until the negative electrode potential is 0V, and read the capacity C1 at this point, which corresponds to C1 / C0SOC; 5) Let it stand for 5 minutes; 6) Charge with 4.5C0 constant current until the negative electrode potential is 0V, and read the capacity C2 at this point, which corresponds to C2 / C0SOC; 7) Let it stand for 5 minutes; 8) Charge with 4C0 constant current until the negative electrode potential is 0V, and read the capacity C3 at this point, which corresponds to C3 / C0SOC; 9) Let it stand for 5 minutes; 10) Charge with 3C0 constant current until the negative electrode potential is 0V, and read the capacity C4 at this point. 11) Let stand for 5 minutes; 12) Charge with 2C0 at a constant current until the negative electrode potential is 0V, and read the capacity C5 at this time, which corresponds to C5 / C0SOC; 13) Let stand for 5 minutes; 14) Charge with 1C0 at a constant current until the negative electrode potential is 0V, and read the capacity C6 at this time, which corresponds to C6 / C0SOC; 15) Let stand for 5 minutes; 16) Charge with 0.8C0 at a constant current until the negative electrode potential is 0V, and read the capacity C7 at this time, which corresponds to C7 / C0SOC; 17) Let stand for 5 minutes; 16) Charge with 0.5C0 at a constant current until the negative electrode potential is 0V, and read the capacity C8 at this time, which corresponds to C8 / C0SOC; 15) Let stand for 5 minutes; 16) Charge with 0.33C0 at a constant current until the negative electrode potential is 0V, and read the capacity C9 (i.e., C0), which corresponds to 100%SOC. The required charging time is obtained by summing the total charging time from 10% SOC to 80% SOC.

[0271] III. Test Results

[0272] The test results of the above embodiments and comparative examples are shown in Tables 1, 2 and 3.

[0273] Table 1

[0274]

[0275] Table 2

[0276]

[0277] As can be seen from the examples and comparative examples, the negative electrode active material includes a core and a coating layer that covers at least part of the surface of the core. The core includes microcrystalline graphite, and the coating layer includes amorphous carbon. The roundness of the negative electrode active material is 0.65-0.95, which is beneficial for balancing the energy density and fast charging performance of the battery.

[0278] Table 3

[0279]

[0280] As can be seen from the comparison between Examples 1-2 and Example 3, the roundness of the negative electrode active material is 0.75-0.9, which is beneficial to further improve the specific capacity of the negative electrode active material, improve the energy density of the battery, and take into account the fast charging performance of the battery.

[0281] As can be seen from the comparison between Examples 2, 5 and 4, the coating layer is prepared by heat treatment of asphalt, and the maximum temperature of the heat treatment is 1200℃-1400℃, which is beneficial to further improve the energy density and fast charging performance of the battery.

[0282] As can be seen from the comparison between Example 2 and Example 6, the orientation degree OI value of the negative electrode active material is 1.5-3, which is beneficial to further improve the fast charging performance of the battery while taking into account the energy density.

[0283] As can be seen from the comparison between Examples 2 and Examples 7-8, the particle size distribution curve of the negative electrode active material has two characteristic peaks, including a first characteristic peak and a second characteristic peak. The peak position of the first characteristic peak is smaller than that of the second characteristic peak. The peak position of the first characteristic peak is 3-10 μm and / or the peak position of the second characteristic peak is 14-25 μm, which is beneficial to further improve the energy density and fast charging performance of the battery.

[0284] As can be seen from the comparison between Examples 2 and Examples 9-10, the ratio of the peak intensity of the first characteristic peak to the peak intensity of the second characteristic peak is 0.15-0.3, which is beneficial to further improve the energy density and fast charging performance of the battery.

[0285] As can be seen from the comparison between Example 2 and Example 11, the particle size distribution curve of the negative electrode active material has two characteristic peaks, including a first characteristic peak and a second characteristic peak. The peak position difference between the first characteristic peak and the second characteristic peak is 4-20 μm, which helps to further improve the energy density and fast charging performance of the battery.

[0286] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, It includes positive electrode, negative electrode, and electrolyte; The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a negative electrode active material. The negative electrode active material includes a core and a coating layer that at least partially covers the surface of the core. The core includes microcrystalline graphite, and the coating layer includes amorphous carbon. The roundness of the negative electrode active material is 0.65-0.

95.

2. The battery cell according to claim 1, characterized in that, The roundness of the negative electrode active material is 0.75-0.

9.

3. The battery cell according to claim 1 or 2, characterized in that, The R value of the negative electrode active material is 88%-94%, and can be selected as 88%-92%, where R = 1. G / (I G +I D ), I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.

4. The battery cell according to any one of claims 1-3, characterized in that, The orientation degree (OI) of the negative electrode active material is 0.5-4, and can be selected as 1.5-3.

5. The battery cell according to any one of claims 1-4, characterized in that, The thickness of the coating layer is 1-300nm, and can be selected as 5-200nm.

6. The battery cell according to any one of claims 1-5, characterized in that, The particle size distribution curve of the negative electrode active material has two characteristic peaks, including a first characteristic peak and a second characteristic peak, and the peak position difference between the first characteristic peak and the second characteristic peak is 4-20 μm.

7. The battery cell according to claim 6, characterized in that, The peak position of the first characteristic peak is smaller than that of the second characteristic peak, and the peak position of the first characteristic peak is 0.5-12 μm, optionally 3-10 μm; and / or, the peak position of the second characteristic peak is 6-35 μm, optionally 14-25 μm.

8. The battery cell according to claim 6 or 7, characterized in that, The area ratio of the first characteristic peak to the area of ​​the second characteristic peak is 10:90-50:50, 25:75-40:

60.

9. The battery cell according to any one of claims 1-8, characterized in that, The graphitization degree of the negative electrode active material is greater than or equal to 88%, and can be selected as 90%-96%.

10. The battery cell according to any one of claims 1-9, characterized in that, The oil absorption value of the negative electrode active material is less than or equal to 65, and can be selected as 55-65; and / or, The compacted density of the negative electrode active material under 2T pressure is 1.5-2 g / cm³. 3 The selectable value is 1.55-1.9 g / cm³. 3 .

11. The battery cell according to any one of claims 1-10, characterized in that, The specific capacity of the negative electrode active material is 368-400 mAh / g, and can be selected as 368-390 mAh / g.

12. The battery cell according to any one of claims 1-11, characterized in that, When the battery cell is fully discharged, the compaction density of the negative electrode film is 1.3 g / cm³. 3 -1.85g / cm 3 The option is 1.62 g / cm³. 3 -1.80g / cm 3 .

13. A method for preparing a negative electrode active material, characterized in that, Includes the following steps: Microcrystalline graphite and coating materials are mixed and then heat-treated to obtain a negative electrode active material; The coating material is heat-treated to form a coating layer covering at least a portion of the surface of the microcrystalline graphite. The coating layer includes amorphous carbon, and the roundness of the negative electrode active material is 0.65-0.

95.

14. The preparation method according to claim 13, characterized in that, The coating material includes at least one of resin and asphalt, wherein the asphalt is selected from one or more of petroleum asphalt and bio-asphalt, and the resin is selected from one or more of epoxy resin, phenolic resin, coal tar, urea-formaldehyde resin, and furan resin. Optionally, the coating material includes petroleum asphalt.

15. The preparation method according to claim 13 or 14, characterized in that, The maximum temperature for the heat treatment is 800℃-1400℃, and can be selected as 1200℃-1400℃.

16. The preparation method according to any one of claims 13-15, characterized in that, The process of mixing microcrystalline graphite and coating materials and then heat-treating them to obtain the negative electrode active material specifically includes: Microcrystalline graphite is crushed and graded to obtain first microcrystalline graphite and second microcrystalline graphite. The first microcrystalline graphite, the second microcrystalline graphite, and the coating material are mixed and heat-treated to obtain the negative electrode active material; Wherein, the Dv50 of the first microcrystalline graphite is less than the Dv50 of the second microcrystalline graphite, the Dv99 of the first microcrystalline graphite is less than the Dv99 of the second microcrystalline graphite, the Dv50 of the first microcrystalline graphite is 2-10μm, optionally 3-8μm, the Dv99 of the first microcrystalline graphite is 8-30μm, optionally 12-25μm; and / or, the Dv50 of the second microcrystalline graphite is 5-30μm, optionally 10-25μm; the Dv99 of the second microcrystalline graphite is 28-50μm, optionally 32-47μm.

17. The preparation method according to claim 16, characterized in that, The mass ratio of the first microcrystalline graphite to the second microcrystalline graphite in the negative electrode active material is 10:90-40:60, and can be selected as 15:85-30:

70.

18. A battery device, characterized in that, The battery device comprises a battery cell according to any one of claims 1 to 12 or a negative electrode active material prepared according to any one of claims 13 to 17.

19. An electrical appliance, characterized in that, The electrical device includes the battery device as described in claim 18, the battery device being used to provide electrical energy.

20. An energy storage device, characterized in that, The energy storage device includes the battery device as described in claim 18, the battery device being used to store electrical energy.